Extensor carpi ulnaris injuries in tennis players: a study of 28 cases - Montalvan, B.; Parier, J.; Brasseur, J. L.; Viet, D. L.; Drape, J. L. (British Journal of Sports Medicine, 2006)
Pain on the ulnar side of the wrist is common among elite tennis players. Ten years of experience has allowed identification of a pathology involving the extensor carpi ulnaris (ECU) tendon. On the basis of 28 clinical cases seen over the last five years, three clinical patterns are described: (a) acute instability of the ECU; (b) tendinopathy; (c) ECU rupture. Each of these clinical entities requires a different therapeutic approach. A review of the relevant anatomy is provided.